The Effect of Experiential Marketing on Customer Commitment with Customer Satisfaction as a Mediating Variable at Nuju Coffee Bandar Lampung - Tiara Rizky Cahya; Satria Bangsawan; Nuzul Inas Nabila (Yayasan pendidikan dzurriyatul Quran, 2026)
The rapid growth of the coffee shop industry in Bandar Lampung has intensified competition among businesses, encouraging companies to focus not only on product quality but also on delivering meaningful customer experiences. This study aims to examine the effect of experiential marketing on customer commitment, with customer satisfaction acting as a mediating variable at Nuju Coffee Bandar Lampung. This research employs a quantitative approach using a non-probability purposive sampling technique. Data were collected through questionnaires distributed to 180 respondents who had visited and dined in at Nuju Coffee Bandar Lampung within the last three months. Experiential marketing serves as the independent variable, customer satisfaction as the mediating variable, and customer commitment as the dependent variable. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4.0 software. The results indicate that experiential marketing has a positive and significant effect on customer satisfaction. Furthermore, customer satisfaction has a positive and significant effect on customer commitment. The findings also reveal that customer satisfaction significantly mediates the relationship between experiential marketing and customer commitment. These results demonstrate that experiential marketing plays a crucial role in enhancing customer satisfaction and strengthening long-term customer commitment in the coffee shop industry.